Antologia Grega. Epitáfios (livro VII) - Carlos A. Martins de Jesus (Classica Digitalia: Autores Gregos e Latinos: textos, 2019)
Book VII of the Greek Anthology gathers a total of 748 epigrams that are, in general, epitaphs. Planudes copied 582 of them, of which eleven are not in the Palatinus, and it is uncertain why he excluded the other 179 copied in P. In the form of a dialog or not, since its origins the epitaph stages, even if implicitly, an ephemeral connexion between the deceased and the one who reads it. It is about immortalisation, about the dead keeping a link, by means of memory (mnema), with the world of the livings, achieved when his name is pronounced by the passer-by that reads it in the grave.